POTENSI BIOMASA INDONESIA SEBAGAI BAHAN BAKAR PENGGANTI ENERGI FOSIL - Febijanto, Irhan (Jurnal Sains dan Teknologi Indonesia, 2007)
Indonesia is a country having a big biomass potential. This is proven by the fact tahat experts from many developed countries have visited Indonesia to explore and to utilize biomass waste. Utilizing biomass waste as a substitute for fossil fuel is one of the valuable opportunity to implement CDM project for energy sector in agro industry in Indonesia. In this paper eight kinds of biomass wastes potential in Indonesia were theoretically analyzed, then the results were compared with real condition of the biomass waste in sites. Several sites were explored to investigate eight kinds of biomass waste.The utilization and availability of those biomass waste potential as a fuel for power generation in recent conditon is discussed and then the opportunity level for utilization of the biomass wastes is qualitatively described in this paper.